2018
DOI: 10.1007/s00784-018-2384-3
|View full text |Cite
|
Sign up to set email alerts
|

Dentinal tubule obliteration using toothpastes containing sodium trimetaphosphate microparticles or nanoparticles

Abstract: By the addition of TMP, fluoride toothpastes may occlude the dentinal tubules, with potential to reduce dentin hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
5
25
0
2
Order By: Relevance
“…Those concentrations were based on previous studies that showed the effect of two low‐fluoride dentifrices against tooth erosion containing: 250 ppm F in combination with 0.25% TMP (22) and 500 ppm F in combination with 3% TMP (21). Studies have shown that TMP is capable of binding to the dental substrate through hydroxyl (27) and/or amino sites and this induces the precipitation of calcium phosphate apatite (23, 24), when combined with fluoride in the ratio used in the present study (21, 22, 27). In the present study, cross‐sectional hardness profiles confirmed these data up to 180 µ m depth in the enamel (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Those concentrations were based on previous studies that showed the effect of two low‐fluoride dentifrices against tooth erosion containing: 250 ppm F in combination with 0.25% TMP (22) and 500 ppm F in combination with 3% TMP (21). Studies have shown that TMP is capable of binding to the dental substrate through hydroxyl (27) and/or amino sites and this induces the precipitation of calcium phosphate apatite (23, 24), when combined with fluoride in the ratio used in the present study (21, 22, 27). In the present study, cross‐sectional hardness profiles confirmed these data up to 180 µ m depth in the enamel (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The application time of the 10% H 2 O 2 ‐based gels was 30 min per day for 14 d, as indicated by the manufacturers of the products having the same concentration of H 2 O 2 . After each application, the 10% H 2 O 2 ‐based gels were removed from the enamel surface with the aid of gauze, and the block was washed with deionized water and placed in ultrasound (USC 1400; Unique, Indaiatuba, SP, Brazil) at 40 Hz for 5 min to completely remove any residue of the material (24). Thereafter, the enamel blocks were treated with dentifrices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TMP is adsorbed on the dentin surface, mainly by the amino and hydroxyl groups of collagen [Leone et al, 2008] and hydroxyapatite [Delbem et al, 2014;Amaral et al, 2018], respectively. As is a cyclophosphate, it produces a negative polarity of the surface increases [Neves et al, 2018], enhancing the deposition of calcium phosphate apatite [Favretto et al, 2018]. Furthermore, TMP linked with fluoride can result in significant mineralization, depositing up to 20-40 µm of outer dentin [Favretto et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…When sodium trimetaphosphate NPs have been added, uoride toothpastes can occlude the dentinal canals with a capacity for reducing dentin hypersensitivity. 100 Manikandan et al explored the formation of silver oxide NPs (Ag 2 O NPs) via Ficus benghalensis prop root extract (FBPRE) as a stabilizing and decreasing agent and assessed its antibacterial activities versus dental bacterial strains; higher extract concentrations and time frame have been observed with a considerable enhancement in the formation of NPs. The FBPRE and Ag 2 O NPs combination has been found to display very good anti-bacterial activity against both dental bacteria Lactobacilli sp and Streptococcus mutans.…”
Section: Dental Applications Of Nanomaterialsmentioning
confidence: 99%